2021
DOI: 10.1186/s12865-021-00423-x
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 and type 3 innate lymphoid cells at the maternal-fetal interface: implications in preterm birth

Abstract: Background Preterm birth (PTB) is one of the major causes of neonatal morbidity and mortality worldwide. It is commonly accepted that the act of giving birth is the final step in a proinflammatory signaling cascade, orchestrated by an intrauterine milieu coupled to hormonal cues. Consequently, the inflammatory process plays a pivotal role during the pathogenesis of human labor, both in term and preterm deliveries. The ability of innate lymphoid cells (ILCs) to act as pro-inflammatory mediators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Moreover, ILC2 is the most abundant ILC subset in murine uterus [ 22 ], indicating their underline effect in maintaining normal pregnancy. The dynamic changes of ILC subsets in human decidua and murine uterus suggest an important role of ILCs in maintaining healthy pregnancy, and an abnormal increasing of ILC subsets may lead to a pathologic pregnancy, such as preterm labor [ 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ILC2 is the most abundant ILC subset in murine uterus [ 22 ], indicating their underline effect in maintaining normal pregnancy. The dynamic changes of ILC subsets in human decidua and murine uterus suggest an important role of ILCs in maintaining healthy pregnancy, and an abnormal increasing of ILC subsets may lead to a pathologic pregnancy, such as preterm labor [ 19 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The question of decidual lymphocyte traffic is especially relevant as human studies suggest that as many as three dNK cells subsets exist, distinguished by cell surface receptors and transcriptional/functional programming ( 13 ). Similarly, innate lymphoid cells (ILCs) have been identified in both the murine ( 11 , 25 , 26 ) and human decidua ( 8 , 27 , 28 ) and have been associated with pre-term birth ( 29 , 30 ). Although ILCs are found in circulation, they are most abundant at mucosal sites ( 31 , 32 ).…”
Section: Introductionmentioning
confidence: 99%
“…This interaction plays a fundamental role in the induction of intestinal commensal bacteria tolerance [49]. Although altered ILCs numbers have been described in disturbed pregnancies, the role of ILCs in fetal tolerance has not been studied extensively yet [50][51][52][53][54][55]. Our group has previously observed that ILCs reduce their antigen presentation potential during pregnancy, and that uterine ILCs retain a low presentation potential [18].…”
Section: Discussionmentioning
confidence: 99%